Pengantar Studi Madrasah Hadis - Mutaqin, Rizal Samsul; Solihin, Firman (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2022)
The position and function of hadith which is very vital in Islamic teachings has become a driving factor for hadith experts to continue to maintain and maintain hadith from generation to generation. This care and maintenance began in the time of friends, and has never stopped until now. It was the friends and tābi'īn who initially spread to various regions carrying the mission of spreading hadith by organizing scientific circles (halaqah) in these areas. In its development, in these areas—which were fronted mainly by different companions—then a hadith study community was formed, each of which had its own characteristics, which were influenced by regional conditions and brought influence in the field of hadith to the area. These communities are called by contemporary hadith researchers the “Madrasah Hadith.” This paper aims to discuss “Madrasah Hadith,” starting from the definition, urgency, and technical steps of the study, as a reference for researchers who are interested in conducting this study. This research is a type of qualitative research using historical methods. The approach used is descriptive-analytic with data collection techniques usinglibrary research. The results of this study indicate that the Hadith Madrasa is a "community of narrators and hadith experts with the same characteristics between one member and another, related to the media for delivering and maintaining hadith, both riwāyah and dirāyah, at a certain time and place." There are at least six technical steps that must be taken by anyone who wants to conduct a study on Madrasah Hadith.